Natural beauty : a novel - Huang, Ling Ling, 1989- (Dutton, an imprint of Penguin Random House LLC, 2023)
"In this sly, surprising, and razor-sharp debut novel, a virtuoso pianist gives up her future as a musician to work at a high-end wellness store in New York City where the pursuit of beauty comes at a staggering cost. Our narrator is the youngest student at the Conservatory. She produces a sound from the piano no one else does, employing a special technique she learned from her parents-also stunningly talented musicians-who fled China in the wake of the Cultural Revolution. But when an accident leaves her parents debilitated, she abandons her future as a pianist and accepts a job at a high-end beauty and wellness store in New York City. Holistik is known for its remarkable products and outrageous procedures: remoras that suck cheap Botox from the body, eyelash extensions made of spider silk, emotional support ducklings bred to imprint on their owners. Every product is ethically sourced and made with nothing but the highest quality ingredients. Our narrator's new job is a coveted one among New York's beauty-obsessed, and it affords her entry into a new world of privilege. She becomes transfixed by Helen-a model, and the niece of Holistik's charismatic owner-and the two strike up a close friendship that hazily veers into more. All the while, Holistik plies our narrator with products that slim her thighs, smooth her skin, lighten her hair, and change her eye color. But beneath these fancy creams and tinctures lies a terrible truth that threatens to consume her. After all, beauty is nothing without ugliness. NATURAL BEAUTY is a piercing, terrifying, and darkly funny debut that eviscerates the beauty and wellness industry, exploring questions of consumerism, self-worth, race, and identity. This propulsive novel takes a world that feels familiar and pushes it to a conclusion that at first might seem jarring, but when we inch closer, settles on us as truth"--